Meat yield of culled cow and steer carcasses - Pascoal,Leonir Luiz (2009)
The experiment evaluated the meat yield of prepared beef cuts, bone and trimmings of steer and culled cow carcasses. Culled 72-month-old Braford cows, 496 kg live weight and 36-month-old steers, 494 kg live weight were used, all from the same herd and finished on ryegrass pasture. A randomized complete design, with two treatments and 15 replications, was used. Hot carcass weight was lower for cows (248 kg) than for steers (263 kg). Steer carcasses presented better conformation, lower chilling loss, shorter (128.6 vs. 137.7 cm), with longer and thicker limbs compared to cows and similar fat finishing. Steer carcasses showed, compared to cow carcasses, always in the same order, similar side cut yield (13.5 vs. 13.4%), higher forequarter yield (38.4 vs. 37.2%), and lower hindquarter yield (48.1 vs. 48.9%), resulting lower yields of the sub-primal cuts full rump and sirloin, lower rump UK trim, rump tail and striploin. Steer and cow carcasses were similar in total yield of prepared meat cuts (77.8 vs. 77.6%), discarded bone (17.4 vs. 17.9%), discarded trimmings (4.54 vs. 4.09%), and losses inherent to the deboning process (0.34 vs. 0.34%). The results showed that cow carcasses are longer, have shorter and thinner limbs, have higher hindquarter and lower of forequarter yields, but the total yield of prepared meat cuts were similar between cow and steer carcasses.